Synthesis of algorithms of optimization and quasioptimization of space-time noise signal processing to the correlated noise in conditions of complicated motion of aviation hydroacoustic station antenna - Чекед, И. В.; Волковецкий, С. П. (Proceedings of National Aviation University (archive), 1999)
On the basis of earlier developed approaches to optimization of space-time processing with complicated motion of aviation hydroacoustic station antenna in space the series of space-time signal processing algorithms on a background of Gaussian correlated noise were synthesized. The signal consisted of discrete components and a continuous part of a spectrum was considered